Communication Performance Of Millennial Students: Digital Da'wah Strategies Of Islamic Boarding Schools In Lombok West Nusa Tenggara - Athik Hidayatul Ummah (Universitas Islam Negeri (UIN) Mataram, 2023)
The internet and social media have changed people's lifestyles. One form of change is the search for religious references through the internet. Before the internet and massive social media were used, Kyai or Tuan Guru became the main reference and source of religious knowledge. The search for religious knowledge then shifted to virtual spaces so that the religious authority of the messenger was not a priority. This study examines the communication performance of millennial students on social media. The data collection method is descriptive qualitative. The subjects of this study were four Islamic boarding schools, namely Sirajul Huda, Darul Falah, Nurul Haramain and Nurul Hakim Islamic boarding schools. The results of this study indicate that the digital da'wah strategy carried out by Islamic boarding schools in Lombok pays attention to four things, namely the message of da'wah (content), the target of da'wah (audience), da'wah channels (social media), and preachers of da'wah (communicators). These four elements are then framed in an interesting and creative program content on social media so that da'wah is not only related to monotonous lectures, but can be through short films, short videos, podcasts and others.